2008
DOI: 10.2147/ppa.s3205
|View full text |Cite
|
Sign up to set email alerts
|

Patient attitudes toward the use of surgical scrubs in a military hospital clinic

Abstract: ObjectiveTo determine whether obstetrics and gynecology (ob/gyn) patients in a large military teaching hospital have a negative attitude toward the wearing of surgical scrubs by ob/gyn providers.MethodsA convenience sample questionnaire on patient preferences, including two questions relating independently to military and civilian staff attire, was offered to clinic patients over a 2 month period. Univariate and multiple logistic regression analyses were used to identify patient groups less accepting of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The physician attire preferences expressed by patients in this study are consistent with the results of a systematic review of patient preferences in physician attire, which indicated that four of the seven studies on procedural-based specialties like ophthalmology either showed no patient attire preference or preferred scrubs [5]. In the similarly procedure-based specialty of obstetrics and gynecology (OB/GYN), two military clinics at the Portsmouth Naval Hospital [9] and San Diego Naval Medical Center [14] similarly showed that most patients do not have a preference in physician attire but prefer scrubs when they have a preference. In the only other U.S. military setting studied, a general surgery clinic at the William Beaumont Army Medical Center, these results differed from their finding of patient preference for scrubs [10].…”
Section: Discussionsupporting
confidence: 83%
“…The physician attire preferences expressed by patients in this study are consistent with the results of a systematic review of patient preferences in physician attire, which indicated that four of the seven studies on procedural-based specialties like ophthalmology either showed no patient attire preference or preferred scrubs [5]. In the similarly procedure-based specialty of obstetrics and gynecology (OB/GYN), two military clinics at the Portsmouth Naval Hospital [9] and San Diego Naval Medical Center [14] similarly showed that most patients do not have a preference in physician attire but prefer scrubs when they have a preference. In the only other U.S. military setting studied, a general surgery clinic at the William Beaumont Army Medical Center, these results differed from their finding of patient preference for scrubs [10].…”
Section: Discussionsupporting
confidence: 83%
“…10 In the military where uniforms are standard, patients prefer their doctors in white coats over scrubs. 11 In that same environment, nonwhites and Hispanics had higher rates of preference for more formal dress than other groups. Not only do most patients show similar preferences but their parents do, too.…”
mentioning
confidence: 98%